Study of Copolymer Composition on Drug Loading Efficiency of Enalapril in Polymersomes and Cytotoxicity of Drug Loaded Nanoparticles - Danafar, H.; Manjili, H. K.; Najafi, M. (Drug Research, 2016)
Enalapril was used for hypertension and congestive heart failure. Di-block mPEG-PCL copolymers were synthesized and used to prepare of polymersomes for controlled release of enalapril as a hydrophilic drug. The various methods such as HNMR, FTIR, GPC, DSC, PCS and AFM performed for characterization of the polymersomes. The results of AFM showed that the polymersomes had spherical structure and the size of nanoparticles was 97 nm. Drug-loading efﬁciency of nanoparticles from copolymers with compositions of mPEG1-PCL1, mPEG2-PCL2, and mPEG3-PCL3 were 14.43%, 19.8%, and 12.33% respectively. The release profile of enalapril for drug loaded nanoparticles prepared from mPEG3-PCL3 was very fast and release profile for the nanoparticles prepared from mPEG1-PCL1 and mPEG2-PCL2 was sustained. The IC50 value of enalapril was determined to be 8 μM while EPM/m-PEG-PCL nanoparticles did not show significant toxicity at equal concentrations in comparison with enalapril drug. Therapeutic preparations of mPEG-PCL micelle are calibrated by the mouse LD50 assay. A dose-finding scheme of the polymeric micelle showed a safe dose of mPEG-PCL micelles was approximately 330 mg/kg in mice. The relationship between the numbers of animals, number of doses, duration of the assay used to estimate the LD50 and the precision of the assay were investigated. Overall, the results was showed that m-PEG-PCL polymersomes can be considered as a promising carrier for hydrophilic drugs.
Keywords: mPEG-PCL; polymersomes; enalapril; sustained release; cytotoxicity